An Asian introduction to the New Testament - Thomaskutty, Johnson; Sugirtharajah, R. S. (Rasiah S.); Gupta, Nijay K. (Minneapolis, Minnesota : Fortress Press, 2022)
As the Asian context is the cradle of many of the world's religions, the New Testament writings should be interpreted and reinterpreted by accepting their pluriform religious and ideological aspects. Moreover, the existence of multiple Christian denominations demands a doctrinally and conceptually balanced interpretation of the Scriptures. This book will demonstrate inclusive biblical claims within multireligious and multidenominational contexts.
Foreword / R. S. Sugirtharajah -- Preface / Nijay K. Gupta -- Introduction -- The New Testament and the sociocultural and religious realities of the Asian contexts / Kar Yong Lim -- An introduction to Asian biblical hermeneutics / Yung Suk Kim -- The gospel of Matthew / Jae Hyung Cho -- The gospel of Mark / Edwin Jebaraj, Johnson Thomaskutty -- The gospel of Luke / Ekaputra Tupamahu -- The gospel of John / Johnson Thomaskutty -- The book of Acts / Esa Autero -- The letter to the Romans / Arren Bennet Lawrence -- The letters to the Corinthians / Rolex M. Cailing -- The letter to the Galatians / Roji Thomas George -- The letter to the Ephesians / Jayachitra Lalitha -- The letter to the Philippians / Naw Eh Tar Gay -- The letter to the Colossians / Finny Philip -- The letters to the Thessalonians / Andrew B. Spurgeon -- The letters to Timothy / Asish Thomas Koshy -- The letter to Titus / Xiaoli Yang -- The letter to Philemon / Thawng Ceu Hnin -- The letter to the Hebrews / Gilbert Soo Hoo -- The letter of James / Daniel K. Eng -- The letters of Peter / Layang Seng Ja -- The letters of John / Sookgoo Shin -- The letter of Jude / J. Stanly Jones -- The book of Revelation / Biju Chacko.
Includes bibliographical references and index.
Keywords: Bible. -- Introductions; Bible; Christianity and culture -- Asia; Christianity and culture; Asia; Introductions